Nutrient Water Quality of Banica River in Dumaguete City, Philippines 1991-1993 - Dumancas, C; Suarez, P; Juguilon, M.A.; Lozada, R.F.; Patula, M.T; Rubio, N.; Zamora, H. (Silliman Journal, 2023)
The river water of Banica River is analyzed for its pH, dissolved oxygen, biochemical oxygen demand, phosphate-phosphorus, nitrate-nitrogen and ammonia-nitrogen content to establish baseline data. An effective rehabilitation scheme is the expected outcome.